PENGARUH PELATIHAN DAN PENGEMBANGAN SDM TERHADAP KINERJA PEGAWAI DI BADAN PERENCANAAN PEMBANGUNAN DAN PENELITIAN DAERAH KOTA DEPOK JAWA BARAT - Sekar Rinjani; Agung Tri Putranto (Al Hasanah Barokah Foundation, 2025)
This study analyzes the effect of training and human resource development on employee performance at the Regional Development Planning and Research Agency (BAPPEDA) of Depok City. The research used a quantitative method with an associative approach to measure relationships between variables. The population was 58 employees, all taken as samples with a saturated sampling technique due to the small, homogeneous population. Data were collected through questionnaires tested for validity and reliability. Analysis included validity, reliability, classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation) multiple linear regression, correlation coefficient, coefficient of determination, and hypothesis testing with t-tests and F-tests. The results showed all statement items were valid and reliable (Cronbach’s Alpha > 0.6). The classical assumption test indicated data were normally distributed,free from multicollinearity, heteroscedasticity, and autocorrelation (Durbin-Watson = 1.997). Regression analysis revealed training (X1) and human resource development (X2) partially had a positive. Simultaneously, both variables had a significant effect,. In conclusion, training and human resource development, both partially and simultaneously, have a positive, significant effect on BAPPEDA Depok City employees.